My faraway one : selected letters of Georgia O'Keeffe and Alfred Stieglitz. - O'Keeffe, Georgia, 1887-1986; Stieglitz, Alfred, 1864-1946; Greenough, Sarah, 1951- (Yale University Press : in association with the Beinecke Rare Book and Manuscript Library, 2011)
Collects the private correspondence between Georgia O'Keeffe and Alfred Stieglitz, revealing the ups and downs of their marriage, their thoughts on their work, and their friendships with other artists.